Peran Psikologi Komunikasi dalam Membangun Iklim Organisasi Kemahasiswaan Himpunan Mahasiswa Ilmu Komunikasi yang Kondusif - Evie Sophia; Hamidah Hamidah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study examines the role of communication psychology in fostering a conducive organizational climate in the Student Association of Communication Studies (HIMAKOM). The study aims to analyze how interpersonal communication practices, member motivation, conflict resolution, and leadership based on communication psychology contribute to a positive organizational climate. The research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with HIMAKOM administrators, including the chairperson, secretary, and treasurer, as well as participatory observation of organizational activities. The findings reveal that open, routine, and two-way communication plays a crucial role in building a conducive organizational climate. While the formal structure provides a framework, the effectiveness of the organizational climate is largely influenced by psychological factors and the quality of communication among members. The study concludes that the application of communication psychology is not merely a tool for information delivery but a strategic approach to fostering healthy interpersonal relationships, reinforcing value alignment, and creating a productive, harmonious, and conducive organizational climate in HIMAKOM